The Influence of Reading Technique (Skimming Scanning) on Reading Comprehension Achievement on Narrative Text at First Grade Students of MAN 18 Pondok Kopi, Jakarta Timur - Nurchurifiani, Eva (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
The research consists of two variables, the independent variable and dependent variable. Independent variable is reading technique (skimming-scanning) and dependent variable is reading comprehension achievement on narrative text. The objectives of this research is to find out whether there is influence of reading technique (skimming-scanning) on reading comprehension achievement on narrative text.The research method applied is quasi experiment design, it means that the research after the fact. The instrument that is used to collect data is objective test. It consists of 60 items before try out and then after try out only 30 items which have good validity and reliability are used. The population in this research was all first grade students of MAN 18 Pondok Kopi, consisting of 101 students divided in 3 classes. Of these three classes, two of which were used as samples: experiment and control class, respectively consisting of 35 and 31 students. The sampling method is cluster random sampling.The data collected from the samples were then analyzed statistically with t-test, after the data fulfilled the pre requisite tests of normality and homogeneity. The two samples come from normality distribution population since both significances were higher than 0,05, namely 0,119 > 0,05 and 0,179 > 0,05 and thus the H0 is accepted. The homogeneity tests applied to both samples revealed that the variance of the two samples were homogenous: 0.445 > 0,05 for experiment class and 0,245 > 0,05 for control class.The result of statistical calculating using significant 5% (0,05) of t-test with degree of freedom (df) = N1+N2-2 = 66 revealed that sig < 0,05 (0,00 < 0,05). Based on this, the research rejected the null hypothesis (H0) and accepted the alternative hypothesis (H1). Therefore, there is influence of reading technique (skimming-scanning) on reading comprehension achievement on narrative text of the first grade studentsâ at MAN 18 Pondok Kopi, East Jakarta.